2018
DOI: 10.21776/ub.biotropika.2018.006.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Desinfektan dan Lama Perendaman pada Sterilisasi Eksplan Daun Sukun (Artocarpus altilis (Parkinson ex. F.A Zorn) Fosberg)

Abstract: Daun sukun (Artocarpus altilis) merupakan herbal yang banyak dimanfaatkan untuk pengobatan. Kultur jaringan menjadi alternatif dalam meningkatkan produktivitas daun sukun dan metabolit sekunder yang dihasilkannya. Tahap pertama yang menentukan keberhasilan perbanyakan tanaman melalui kultur jaringan adalah teknik sterilisasi. Penelitian ini bertujuan mendapatkan metode sterilisasi terbaik dengan melihat pengaruh penggunaan natrium hipoklorit 5,25% dan alkohol 70% serta waktu perendaman terhadap penurunan konta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…The addition of disinfectants containing sodium hypochlorite for surface sterilization of explants commonly used in many related studies (Felek et al 2015;Setiani et al 2018;Sulistiyo et al 2018;Zinabu et al 2018). Sodium hypochlorite is known to have antibacterial activity by damaging bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of disinfectants containing sodium hypochlorite for surface sterilization of explants commonly used in many related studies (Felek et al 2015;Setiani et al 2018;Sulistiyo et al 2018;Zinabu et al 2018). Sodium hypochlorite is known to have antibacterial activity by damaging bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…External location is the contamination that appears does not reach explants or by the edge of the culture medium. According to Setiani et al (2018), external contamination can come from environment, while internal contamination comes from contaminants that live inside the explants. Other ways to eliminate internal contamination is by giving fungicides and antibiotics into the medium (Kritzinger et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The old explants produced more oxidation than the younger explants [21]. The research results by Setiani et al [22] that sterilization of leaf explants Artocarpus altilis using 5.25% NaOCl for 10 minutes obtained browning explants reaching 90%. Meanwhile, Natasha & Restiani [23] reported that the 5% NaOCl concentration for 5 minutes in the sterilization of Javanese Ginseng leaf Talium paniculatum explants effectively suppressed browning.…”
Section: Percentage Of Browningmentioning
confidence: 99%
“…Kontaminasi yang disebabkan oleh bakteri akan menyebabkan eksplan tanaman menjadi basah karena adanya cairan berupa lendir sedangkan kontaminasi jamur eksplan tanaman akan lebih kering dan akan muncul hifa jamur pada tanaman yang terserang dan biasanya dapat dicirikan dengan garis-garis seperti benang yang berwarna putih sampai abu-abu (Asni et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified